2010
DOI: 10.3375/043.030.0401
|View full text |Cite
|
Sign up to set email alerts
|

Fire Frequency Affects Structure and Composition of Xeric Forests of Eastern Oklahoma

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…The positive responses of forb and C3 graminoid cover and richness and of total understory cover and diversity to increased fire frequency in our study may have resulted, in part, from the significant reduction in density of saplings and shrubs [1.4 m tall at fire frequencies between two and five fires per decade reported elsewhere (Burton et al 2010). A previous study in longleaf pine woodlands in Florida, USA found a reduction in litter production from saplings and shrubs due to their removal by prescribed burning benefitted understory herbaceous plants (Hiers et al 2007).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…The positive responses of forb and C3 graminoid cover and richness and of total understory cover and diversity to increased fire frequency in our study may have resulted, in part, from the significant reduction in density of saplings and shrubs [1.4 m tall at fire frequencies between two and five fires per decade reported elsewhere (Burton et al 2010). A previous study in longleaf pine woodlands in Florida, USA found a reduction in litter production from saplings and shrubs due to their removal by prescribed burning benefitted understory herbaceous plants (Hiers et al 2007).…”
Section: Discussionmentioning
confidence: 68%
“…Fire at frequencies of less than two fires per decade led to declines in herbaceous vegetation most likely due to increased woody shrub and sapling diversity and density (Burton et al 2010). More frequent fire, up to five fires per decade, benefited diversity and biomass of some herbaceous species and disadvantaged woody shrubs and saplings (Burton et al 2010). This information provides the land manager the knowledge to use prescribed fire to create a diverse landscape with patches of vegetation in different conditions depending on the fire frequency.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recognition of this nonlinearity deepens our appreciation of the complexity of the oak-fire relationship. Whereas repeated fire may enhance oak regeneration potential, it can also reduce it if surviving oak stems do not have a sufficiently long fire-free interval to grow past the sapling size class and recruit into the overstory (Dey and Fan 2009, Burton et al 2010, Fan et al 2012.…”
Section: Discussionmentioning
confidence: 99%